Civil society organisations, social innovation and health research in Europe. - Beinare, Dace; Mccarthy, Mark (European Journal of Public Health, 2012)
Background: European Union strategies and programmes identify research and innovation as a critical dimension for future economic and social development. While European research policy emphasizes support for industry, the health field includes not-for-profit civil society organisations (CSOs) providing social innovation. Yet, the perspectives of CSOs towards health research in Europe are not well understood. Methods: STEPS (Strengthening Engagement in Public Health Research) was funded by the European Commission's Science in Society research programme. Within the study, we interviewed by telephone respondents of 13 European health CSOs, which represented collectively local and national organizations. Results: Research was valued positively by the respondents. Health CSOs did not seek to do research themselves, but recognized the opportunity of funds in this field and welcomed the possibility of collaborating in research, of using the results from research and of providing input to research agendas. Links between research and users provides knowledge for the public and improves impacts on policy. Research and evaluation can help in demonstrating the benefit of innovative activities, and give support and legitimacy. However, the cultures of, and incentives for, researchers and health CSOs are different, and collaboration requires building trust, a shared language and for the power relations and objectives to match. Conclusions: Health CSOs contribute social innovation in organising services and activities such as advocacy that cannot be satisfactorily met by industry. Engaging CSOs in research and innovation will strengthen the European Research Area.